Health Assistance (Medical Team) Tourist Activities on Mount Bromo - Sugiarto, Dinta; Evi, Nurul; Sunaryo, Eri Yanuar Akhmad Budi; Rahmatika, Qory Tiffani; Widjayanti, Yhenti; Ramadhan, Muhammad Putra; Masfi, Ahmad; Afiani, Nurma; Yodsuban, Pairin (Inovasi Lokal, 2023)
Purpose: To ensure the safety and health of tourists. They also play a role in maintaining the security of tourists in the area. In addition, the accompanying medical team can also provide health services such as light health checks, simple medical procedures, and providing health information to tourists. Method: This will make it easier for the medical team to provide emergency medical care if there are tourists who need it. This aims to monitor the health of tourists and provide first aid if there are tourists who need it. Must-have medical equipment such as defibrillators, oxygen, resuscitation equipment, and so on. This can include how to manage common health symptoms and steps to prevent disease. Result: Several cases were encountered in the health assistance, namely: bruises (contusions), cramps and bleeding. Conclussion: Traveling to the mountains can cause serious injury if proper precautions are not taken. In addition, it is important to follow the guidelines given by experienced climbers, avoid trails that are too dangerous, and not take excessive risks when doing activities on the mountain. With proper preparation and wise precautions, we can reduce the risk of injury and enjoy a safe and enjoyable mountain travel experience